Dynamic response of symmetrical and asymmetrical sandwich plates with shear thickening fluid core subjected to penetration loading. (15th March 2016) - Tan, Z.H.; Zuo, L.; Li, W.H.; Liu, L.S.; Zhai, P.C.
Abstract: Symmetrical and asymmetrical sandwich plates with a shear thickening fluid (STF) core were designed to be penetrated by a cylindrical projectile at various impact velocities. These STFs consist of SiO2 /PEG400, and the volume fractions of SiO2 nano-particles are 54% and 56%, respectively. Failure mode of the rear face sheet of the symmetrical sandwich plate is petal perforation, but the rear face sheet of the asymmetrical sandwich plate failed in plug perforation mode at the velocity of less than 80 m/s and in the petal perforation mode at the velocity faster than 90 m/s. The results showed that both the face sheet and the STF core played different roles in impact resisting properties and energy absorption of the sandwich plate at different impact velocities. The thickness of the rear sheet has a significant influence on the energy absorption at low impact velocity, while this influence can be ignored at high impact velocity. The effects of the particle volume fraction, impact velocity and thickness of rear face sheet on the deformation mechanism and energy absorption of the sandwich plate were also discussed. Graphical abstract: Highlights: The sandwich plates with a STF core were penetrated by a cylindrical projectile at various impact velocities. The face sheet and STF core played different roles in the failure mechanism of the sandwich plates under impact loading. The energy absorption of 56% STFs was more than that of 54% and increased with the increasing of the impact velocity. The difference between the energy absorbed by the 54% and 56% STFs decreased as the impact velocity is more than 90 m/s.